Recurrent Wheezing In Preschool Children; The Associated Factors. A Cross Sectional Study In Tertiary Care Hospital - Mumtaz, Shaista; Farooq Ikram; Sarah Javed; Asbah Rahman; Ammara Jamil; Atif Naseem Abbasi (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine associated factors in preschool children presenting with recurrent wheezing to children out patient department. Study Design: Cross sectional study. Place and Duration of Study: Pediatrics department, Pak Emirates Military Hospital Rawalpindi from April 2019 to January 2021. Methodology: 300 children with age 2-5 year presenting with recurrent wheezing to children outpatient department were included in the study. Vitamin D levels were carried out in all of them and levels of <20ng/ml was considered as deficient. Gender, breastfeeding status, serum Ig E levels and socioeconomic status of family were correlated with the presence of Vitamin D deficiency amongst children suffering from recurrent wheezing. Results: Out of 300 preschool children with recurrent wheeze, 213(71%) showed the presence of vitamin D deficiency while 87(29%) had normal vitamin D levels. 179(59.7%) patients were male and 121(40.3%) patients were female. Mean age of the patients was 3.4±3.211 years. After applying the binary logistic regression, we found that low socioeconomic status and breastfeeding the child for less than 6 months had significant association with the presence of vitamin D deficiency amongst preschool children with recurrent wheeze. Conclusion: Vitamin D deficiency emerged as a common finding amongst preschool children presenting with recurrent wheeze at our tertiary care hospital in Pakistan. Children who were not adequately breastfed or were from families with low income were more at risk of having vitamin D deficiency in our study.